Neurodevelopmental outcome of the high risk infant in Cape Town - Thompson,Mary Clare (Department of Paediatrics and Child Health, 2017)
The outcome of high risk infants provides an important audit of neonatal care. This audit renders valuable information to clinicians, parents and health care planners. Available outcome data from the developing world are sparse and urgently needed. This work was compiled with three aims in mind: to provide data from Cape Town on outcome of high risk infants (including both infants of very low birthweight and infants who have survived hypoxic ischaemic encephalopathy); to evaluate selected early neurodevelopmental assessments of these infants; and to propose a protocol for their effective follow-up. Three separate cohorts were selected and studied in order to achieve these aims. A prospective six-year follow-up study of infants with birth weights less than 1250 g was undertaken at Groote Schuur Hospital's Neonatal Intensive Care Unit. The aim of the study was to document the morbidity, mortality and neurodevelopmental outcome of these infants. Of 235 liveborn infants, 143 (61 %) survived to discharge. Better survival was documented for infants who weighed more than 900 g and were over 30 weeks gestation and whose mothers attended antenatal care. One hundred and six infants (83% of survivors) underwent clinical assessment at one year of age and were evaluated with the Griffiths Scales of Mental Development. Ninety six (91 %) of these survivors were seen and tested at two years of age and 80 (76%) were seen at six years of age together with 70 matched controls who had normal birthweights. Of the 106 infants assessed at one year of age, six infants were diagnosed as cerebral palsied, six were globally developmentally delayed without signs of cerebral palsy and one infant showed significant motor delay with a normal developmental quotient. At two years of age one further infant had cerebral palsy and nine more infants were developmentally delayed. At six years of age five infants had cerebral palsy, one was intellectually disabled and three were intellectually borderline. The major disability rate at one year of age was 11%, at two years of age was 22% and at six years of age was eight percent. The incidence of low birthweight children with possible learning disability was three times that of their matched controls and overall, the low birthweight children scored significantly less in all developmental measures. Forty-five infants who developed hypoxic ischaemic encephalopathy after birth were studied prospectively. A numeric scoring system for the assessment of hypoxic ischaemic encephalopathy during the neonatal period which had previously been developed at Groote Schuur Hospital was tested. The value of the score in predicting neurodevelopmental outcome at one year of age was assessed. Thirty five infants were evaluated at 12 months of age by full neurological examination and the Griffiths Scales of Mental Development. Five infants were assessed at an earlier stage, 4 who died before 6 months of age and one infant who was hospitalised at the time of the 12-month assessment. Twenty three (58%) of the infants were normal, 17 (42%) were abnormal, 16 with cerebral palsy and one with developmental delay. 25 infants were re-evaluated at 3 years of age. 15 of these 25 had been normal at one year of age and were evaluated with ten controls who had had an uneventful perinatal course. The Hypoxic lschaemic Encephalopathy Score was highly predictive for outcome. The best correlation with outcome was a combination of the peak score and evaluation on day seven; giving a positive predictive value of 92% and a negative predictive value of 100% for abnormal outcome, with a sensitivity of 100% and specificity of 93%. At three years of age the HIE survivors without cerebral palsy scored as well as their matched controls on Griffiths developmental evaluation. In these normal survivors no correlation between severity of HIE and developmental quotient was demonstrated. Infants with neurodevelopmental abnormality need to start therapy early and because of this, should be detected as soon as possible. Currently, no widely accepted method of early evaluation exists. A Perinatal Risk Rating, the Dubowitz Neurological Assessment and the Infant Neuromotor Assessment were compared in terms of predicting neurodevelopmental outcome at one year of age. A cohort of 130 consecutive neonatal intensive care unit graduates were selected according to high risk criteria. Each infant was examined at term gestational age on the Dubowitz Neurological Assessment and a Perinatal Risk Rating was allocated. The study infants were seen again at 18 weeks corrected age, when an Infant Neuromotor Assessment was done, and at one year of age the Griffiths Scales of Mental Developmental and full neurological examination were carried out. Of the 130 infants assessed at term, all were seen at 18 weeks. Thereafter five were lost to follow-up and two died. The outcome of all the remaining 123 infants is known. Prediction of a normal outcome at 1 year of age on the Dubowitz Neurological Assessment was 96% and for the Perinatal Risk Rating, 98%, but for an abnormal outcome they predicted only 56% and 42% respectively. The Infant Neurological Assessment at 18 weeks of age predicted a normal outcome at one year in 99% and an abnormal outcome in 82%. Very low birthweight infants are at higher risk for cerebral palsy and intellectual disability. In Groote Schuur Hospital, at six years of age, the major disability rate for infants with birthweights less than 1250 g was eight percent. Forty percent of term infants who survived hypoxic ischaemic encephalopathy had cerebral palsy with associated intellectual disability. The use of the Perinatal Risk Rating is appropriate in newborn facilities where cranial ultrasound is available. Otherwise the Dubowitz Neurological Assessment is an appropriate screening tool in the newborn period. Use of the Hypoxic Ischaemic Encephalopathy Score is recommended for clinical evaluation, prognostication and risk rating. It is proposed that high risk infants should be evaluated at 18 weeks corrected age with the Infant Neuromotor Assessment at a tertiary centre. If this assessment is normal, the infant can then be discharged to community clinic follow-up. Infants with more than one deviant sign at this age need continued review and those with more than three signs should be referred for neurodevelopmental therapy to a comprehensive neurodevelopmental clinic. Even those high-risk infants whose assessments are normal should be enrolled in a pre-school centre at five years of age to facilitate detection of learning problems prior to school entry.